ANALISIS KESESUAIAN IMPLEMENTASI AKAD WADIAH YAD DHAMANAH PADA PRODUK BSI EASY WADIAH BERDASARKAN FATWA DSN-MUI NO.02/DSN-MUI/IV/2000 - Muhammad Irfan Bahtiar S; Amanda Salsabila; Naufal Zihni Mubarok; Reinhard Farid Al Hakim; Muhammad Muammar Raychan; Meilia Dwi Gunawan; Via Audina; Harsono Edwin Puspita (Nusantara Hasana Journal, 2026)
This study aims to analyze the conformity of the implementation of the Wadiah Yad Dhamanah contract in the BSI Easy Wadiah product with the provisions of DSN-MUI Fatwa No. 02/DSN-MUI/IV/2000 concerning Savings Accounts. The research employs a qualitative approach using a descriptive-analytical method and a library research design. Data were collected from scientific journals, DSN-MUI fatwas, reports of Bank Syariah Indonesia, reports of the Financial Services Authority (OJK), and various relevant literature sources. The findings indicate that the implementation of the Wadiah Yad Dhamanah contract in the BSI Easy Wadiah product is in accordance with applicable Islamic principles. The funds deposited by customers are categorized as safekeeping deposits that can be withdrawn at any time, while the bank acts as the custodian authorized to manage the funds for operational activities and Sharia-compliant financing, while guaranteeing the full return of the deposited funds. Furthermore, the mechanism for granting bonuses to customers is voluntary and not stipulated in the initial contract, thereby avoiding any element of riba (usury). The BSI Easy Wadiah product also offers various benefits, including exemption from monthly administrative fees, transaction flexibility, and a low initial deposit requirement. Nevertheless, some customers still have limited understanding of the differences between the wadiah contract and other contracts used in Islamic banking. Therefore, greater educational efforts and socialization programs are needed to strengthen public literacy regarding Islamic finance.